Effects of a 12-Week Web-Based Weight Loss Program for Adults With Overweight and Obesity on COVIDAge and Lifestyle-Related Cardiometabolic Risk Factors: A Randomized Controlled Trial - Brame, Judith; Centner, Christoph; Berg, Niklas; Bartlam, Matt; Gollhofer, Albert; König, Daniel (Frontiers in Public Health, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has induced unhealthy lifestyles, particularly an increase in overweight and obesity, which have been shown to be associated with an increased risk of unfavorable COVID-19 outcomes. Web-based health programs could be a helpful measure, especially in times of severe restrictions. Therefore, the present study aimed to investigate the effects of regular attendance in a 12-week web-based weight loss program on COVIDAge, a new construct for risk assessment of COVID-19, and lifestyle-related cardiometabolic risk factors. N = 92 subjects with overweight and obesity (50.0 ± 10.8 years, 76.1% females, 30.5 ± 2.1 kg/m2) of this randomized controlled trial, which were assigned to an interactive (ONLINE: intervention group) or non-interactive (CON: control group) web-based weight loss program, were included in the data analysis. COVIDAge and cardiometabolic risk factors, including anthropometric outcomes, blood pressure, flow-mediated dilatation, and blood parameters, were assessed before and after the 12-week intervention phase. There was a significant group difference in the change of COVIDAge (ONLINE: -4.2%, CON: -1.3%, p = 0.037). The ONLINE group also showed significantly greater reductions in anthropometric outcomes and systolic blood pressure than the CON group (p < 0.05). To the authors’ knowledge, this was the first study investigating the effects of regular attendance in a web-based health program on lifestyle-related risk factors for COVID-19. The results demonstrated that adults with overweight and obesity can improve their COVIDAge and specific cardiometabolic risk factors by using this interactive web-based weight loss program regularly. However, this needs to be confirmed by future studies. This study is registered at the German Clinical Trials Register (DRKS00020249, https://www.drks.de).